Influence of zirconia on microstructure of bioactive glass coated on stainless steel for biomedical application - Rabiee, S. M.; Azizian, M.; Nourouzi, S. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/